2022
DOI: 10.1038/s41433-022-01968-w
|View full text |Cite
|
Sign up to set email alerts
|

Increased intravitreal glucose in rhegmatogenous retinal detachment

Abstract: Altered glucose metabolism, along with low-grade inflammation, has been proposed to be involved in retinal detachment (RD)-induced cone loss. Here, we assessed intravitreal glucose and cytological profile in patients with macula-off RD. METHODS: Glucose concentration was analysed in vitreous samples from 137 non-diabetic patients undergoing vitrectomy for either primary macula-off RD (n = 73) or epiretinal membrane (ERM; n = 64). Cellularity was assessed in vitreous cytospin preparations by a semi-quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Other contributing factors included modifiable factors, such as APTT, BASP, GLB, GLU, MPV, PCT, and UA. Arndt C and colleague [ 22 ] found that intravitreal glucose concentration was higher in the RD group. Moreover, APTT, BASP, GLB, MPV, PCT, and UA indicate the whole body’s general homeostasis and inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other contributing factors included modifiable factors, such as APTT, BASP, GLB, GLU, MPV, PCT, and UA. Arndt C and colleague [ 22 ] found that intravitreal glucose concentration was higher in the RD group. Moreover, APTT, BASP, GLB, MPV, PCT, and UA indicate the whole body’s general homeostasis and inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Routine blood indices, biochemical indices, and coagulation indices can reflect a wide range of physiological and pathological states in the body [ 20 ], providing information on aspects such as inflammation, blood circulation, metabolic status, and tissue injury. Research indicates that blood markers of inflammation [ 21 ], glucose levels [ 22 ], and lipid levels [ 23 ] are associated with an increased risk of ocular diseases, including HM, and RD. Our previous study developed a routine blood parameters-based model for serial monitoring and predicting the occurrence of RD in HM [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although surgery is an effective way to reattach the neurosensory and retinal pigment epithelium (RPE) layer, functional restoration requires more than physical recovery. 3 , 6 8 The degeneration of PR outer segments happens soon after detachment, but their recovery takes a long time after reattachment. 9 Thus, an effective therapeutic intervention is needed to protect PR from death and to improve their functional recovery.…”
mentioning
confidence: 99%